2020
DOI: 10.2147/ott.s240028
|View full text |Cite
|
Sign up to set email alerts
|

<p>EMP1 Promotes the Proliferation and Invasion of Ovarian Cancer Cells Through Activating the MAPK Pathway</p>

Abstract: Introduction: Epithelial membrane protein 1 (EMP1), a member of the EMP family, is overexpressed in a large number of tumors and is thought to be a cellular connexin on the cell membrane and is involved in proliferation, invasion, metastasis of tumor cells, and epithelial-mesenchymal transition (EMT). Nevertheless, its biomedical function in ovarian cancer is still unclear. Methods: EMP1 was detected in ovarian cancer cell lines by whole transcriptome resequencing. The mRNA of EMP1 was examined by qRT-PCR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…As the full picture of miRNA-mRNA networks has yet to be accomplished [56], the results presented here may be helpful to find key regulators of OC network. In line with our findings, all 6 miRNAs (hsa-miR-126-3p, hsa-miR-223-3p, hsa-miR-23a-5p, hsa-miR-27a-5p, hsa-miR-486-5p, and hsa-miR-506-3p) and 8 mRNAs (ATF3, CH25H, EMP1, HBB, HBEGF, NAMPT, POSTN, and PROCR) have been previously shown to play an essential role in ovarian carcinogenesis with respect to different aspects such as OS, histological subtype, clinical stage, chemoresistance, or treatment [19,20,27,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. We reported previously that hsa-miR-23a-5p, hsa-miR-27a-5p, and hsa-miR-126-3p, were significantly associated with OS in the same EOC cohort (p < 0.01, univariate Cox regression analysis) [27].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…As the full picture of miRNA-mRNA networks has yet to be accomplished [56], the results presented here may be helpful to find key regulators of OC network. In line with our findings, all 6 miRNAs (hsa-miR-126-3p, hsa-miR-223-3p, hsa-miR-23a-5p, hsa-miR-27a-5p, hsa-miR-486-5p, and hsa-miR-506-3p) and 8 mRNAs (ATF3, CH25H, EMP1, HBB, HBEGF, NAMPT, POSTN, and PROCR) have been previously shown to play an essential role in ovarian carcinogenesis with respect to different aspects such as OS, histological subtype, clinical stage, chemoresistance, or treatment [19,20,27,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. We reported previously that hsa-miR-23a-5p, hsa-miR-27a-5p, and hsa-miR-126-3p, were significantly associated with OS in the same EOC cohort (p < 0.01, univariate Cox regression analysis) [27].…”
Section: Plos Onementioning
confidence: 99%
“…In another study, high expression of HBB has been proposed as a predictor for a shorter 5-year survival and has been shown to be associated with drug resistance in OC based on the microarray data from different resources: TCGA Ovarian Statistics, Bonome Ovarian Statistics, Yoshihara Ovarian Statistics, Lu Ovarian Statistics and Welsh Ovarian Statistics [65]. Liu et al presented that epithelial membrane protein 1 mRNA (EMP1) has been up-regulated in 34 OC tissues samples when compared with corresponding noncancerous ovarian epithelial tissues [66]. Moreover, in the same study, EMP1 expression has been linked with clinical classification, metastasis, and survival prognosis in OC.…”
Section: Plos Onementioning
confidence: 99%
“…EMP1 has been reported to suppress tumor progression across various cancer types, including nasopharyngeal cancer, oral squamous cell carcinoma and prostate cancer [ 38 , 40 , 41 ]. On the contrary, EMP1 has been shown to be involved in cancer progression, including ovarian cancer and pediatric leukemia [ 42 , 43 ], which suggests that the anti-tumor or tumor-promoting action of EMP is dependent on the type of cancer. Some studies have demonstrated that EMP1 can regulate the PI3K/AKT pathway [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 , 23 ] EMP1 promotes the proliferation and invasion of ovarian cancer cells by activating the MAPK pathway. [ 24 ] C-myc, a common over-activated oncogene by amplification, has been found in >70% of the advanced ovarian cancer patients. [ 25 , 26 ] ITGAM is a potentially significant gene which plays a key role in the metastasis of high-grade serous ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%